Composing Self on Narrative Landscapes of Sexual Difference: A Story of Wisdom and Resilience - Estefan, Andrew; Roughley, Robert A. (Canadian Journal of Counselling and Psychotherapy, 2012)
This study draws upon recent narrative inquiry research that explored the resilience experiences of 6 young same-sex-attracted men and women (4 men, 2 women; age range = 21–27). This article elucidates the story of one participant, Joseph, a 25-year-old Canadian man. As we conducted the research, Joseph’s story stood out for us as having something important to say about resilience and same-sex attraction. Using a three-dimensional narrative inquiry space, the researchers and participants encountered Joseph’s story of resilience as a situated wisdom that arises in experience that is social, temporal, and situated. This perspective of resilience calls upon mental health professionals to enter into the client’s story and to live and practice within it.